HYDROPHOBICITY ENHANCEMENT OF PVDF-HFP MEMBRANE INDUCED BY POLYDIMETHYLSILOXANE-GRAFTED-SILICA NANOPARTICLES FOR MEMBRANE GAS ABSORPTION - TOH , MOAU JIAN (2020)
Membrane gas absorption (MGA) is a promising technology for carbon dioxide removal from flue gas stream to reduce global warming. Membrane acts as the non-selective barrier between the mix gas and liquid absorbent by allowing the diffusion of CO2 via pressure difference. For stable operation, the pores of the membrane need to be non-wetted as pore wetting increases the mass transfer resistance to gas transport. Currently, hydrophobic membrane still suffers from severe wetting over prolonged periods of operation. In order to mitigate the tendency of pore wetting, membrane hydrophobicity has been enhanced via incorporation of hydrophobic nanoparticles. Nevertheless, the nanoparticles used were consisted of short hydrophobic functional groups which imparted moderate hydrophobicity on membrane surface.